Economies of Size and Scope in Rural Low-Volume Roads - Deller, Steven C.; Chicoine, David L.; Walzer, Norman (The Review of Economics and Statistics, 1988)
Evidence on cost savings from reorganizing township low-volume, rural-road systems into larger units is presented in the study of technical efficiencies in producing local government services. Data are from a sample of midwestern townships. Heterogeneity of surface types is accounted for by specifying a multiple output translog cost function. Examination of economies of size suggest that cost savings could be realized by reorganizing townships into larger units. The presence of economies of scope suggest that jurisdictions should not specialize in maintenance responsibilities due to the joint use of inputs. Copyright 1988 by MIT Press.